Within-host microevolution of Streptococcus pneumoniae is rapid and adaptive during natural colonisation - Chrispin Chaguza (Nature Portfolio, 2020)
Streptococcus pneumoniae is an opportunistic pathogen and asymptomatic colonization is a precursor for invasive disease. Here the authors show rapid within-host evolution of naturally acquired pneumococci in ninety-eight infants driven by high nucleotide substitution rates and intra-host homologous recombination.